DEVELOPMENT OF SOCIAL EDUCATION INNOVATIONS IN INFORMATICS AND MULTIDISCIPLINARY BASES TO IMPROVE THE WELFARE OF SOCIETY IN INDONESIA - Haerani, Reni (Yayasan Meira Visi Persada, 2024)
Social education plays a crucial role in shaping the character of the younger generation and understanding societal well-being issues. Information-based education is essential in global technological development, including in Indonesia. Therefore, innovations related to social education must be increasingly emphasized for the welfare of society. This research adopts a qualitative approach, facilitating the analysis of social contexts, perceptions, and experiences comprehensively. The findings reveal the interconnectedness of education and social sciences, with education-designing curricula beneficial for society. In terms of societal well-being, social education innovations stress the use of internet-based technology and a multidisciplinary approach contributing positively to community life. This form of social education seems capable of significantly impacting the insights, attitudes, values, and behaviors of a society becoming more open to the developments of the modern world.